Enhanced scab resistance in apple conferred by Rvi6 and polyploidy is linked with distinct shifts in the phenolics profile - Švara, Anže; Mikulič Petkovšek, Maja; Veberič, Robert; Keulemans, Wannes; De Coninck, Barbara; Carpentier, Sebastien; De Storme, Nico (Nature Portfolio, 2025)
Apple (Malus × domestica Borkh.) production is threatened by scab, caused by the fungus Venturia inaequalis. One defense mechanism of apple trees against fungal pathogens such as V. inaequalis is the biosynthesis of antifungal compounds. Amongst these, phenolic compounds are particularly hypothesized to correlate with scab resistance, thereby offering a putative route to breed new apple cultivars with enhanced resistance. To characterize the involvement of phenolics in scab resistance, as conferred by either the Rvi6 resistance gene or through increased somatic ploidy, we monitored the phenolics profile in the leaves of apple genotypes harboring Rvi6 or increased ploidy that show enhanced levels of scab resistance compared to susceptible genotypes. Our study revealed differences in total and specific phenolic contents across the tested genotypes with significant correlation to Rvi6-based resistance and a minor effect of polyploidy herein. In particular, procyanidin dimer levels appeared positively correlated with the level of resistance, indicating a putative functional role in scab resistance. In contrast, the majority of other phenolics were negatively correlated with the resistance. Finally, our study did not identify a significant correlation between reduced phloridzin:flavanol ratio and Rvi6 resistance. These findings are discussed in the context of the role of phenolic metabolism in apple scab resistance.